How policing has changed since COVID-19 - Asif Rashid (The Journal of Intelligence, Conflict and Warfare, 2021)
Superintendent Asif Rashid of Calgary Police discussed policing changes since COVID-19 on November 26, 2020 at the 2020 CASIS West Coast Security Conference. The presentation was followed by a question and answer period with the other speakers of the panel. The key points discussed were how policing was changed to adapt to the challenges of COVID-19, emergency management systems, and technological issues.